Alternative indicators: can socio-economic advancement be measured? - Sziget, Cecília; Borzán, Anita; Farkas, Szilveszter (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2013)
The target of our study is to examine the possibilities as well as the limitations of the application alternative composite indicators. Our study focuses on what kind of relations the indicators are in; to what extent they can substitute the GDP and what kind of morals can be indicated for Hungary. The basic question of our research is how possible is to group countries clearly based on the valuesof alternative indicators. In this study three composite indicators (HDI, HPI, EPI) and the ecological footprint and GDP trends were examined. In the first phase of our research, we revealed that these indicators could be observed in pairs to linear relationship; the Pearson’s correlation index values are shown in the correlation matrix. Based on our analysis, these two indicators are independentfrom each other and also independent from the GDP; these are the HPI and the EPI. The classification of countries was performed using cluster analysis. Basedm on the three-cluster model, a specific path of development was determined in Latin America, which proves a useful experience for Hungary.